PENGARUH BUDAYA ORGANISASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT FASTFOOD INDONESIA Tbk. (KFC CABANG DEMANG LEBAR DAUN) PALEMBANG - Syahyuni .; Tio Erdhiansyah Pratama (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
This study is to determine the influence of Organizational Culture and Communication on Employee Performance at PT.Fastfood Indonesia Tbk. (KFC branch of Demang Lebar Daun) Palembang with a population of 59 employees, and a sample of 59 people. The data collection technique is done through the division of questionnaires and processed statistically with the method of multiple aggression analysis with Y = a + b1 X1 + b2X2 + edan processed with SPSS 17 program. Validity of test results obtained rhitung> rtabel for each itempernyataan and reliability testing of questionnaires obtained value of each variabelyaitu 0757 for the variables X1, X2 0771's, as well as 0.765untuk variable Y. This value describes the reliability values> 0.60, meaning that the value of The research instrument is reliable and can be used as a measuring tool is analyzed selanjutya. Data analysis of each variable obtained multiple linear regression equation Y = 6.694 + 0.313 X1 + 0.732 X2 + e. Obtained Adjusted R Square value of 0.410, which means X1 and X2 explain the effect on variable Y by 41%, while the remaining 59% described other variables outside the study. From the results of test calculations simultansebesar 21 166 with Ftabel of 3:16 yangartinya Fhitung> Ftabeldengan significant value of 0.005, which means that organizational culture and komunikasisecara together have an effect simultaneously to employee performance at KFC branch Lebar Daun demat Palembang. From the resulting partial test each bebasberpengaruh significant variables on the dependent variable, denganBudaya Organization has a significance level of less than 0.05, so the hypothesis is accepted while variable memilikisignifikansi Communication is also smaller than 0,005 studies that the hypothesis is accepted.Keywords: Organizational Culture, Communication, and Employee Performance